2018
DOI: 10.1155/2018/9713259
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogenol® Induces Browning of White Adipose Tissue through the PKA Signaling Pathway in Apolipoprotein E-Deficient Mice

Abstract: Beige adipocytes in white adipose tissue (WAT) have received considerable recognition because of their potential protective effect against obesity. Pycnogenol (PYC), extracted from French maritime pine bark, has anti-inflammatory and antioxidant properties and can improve lipid profiles. However, the effect of PYC on obesity has never been explored. In this study, we investigated the effects of PYC on obesity and WAT browning in apolipoprotein E- (ApoE-) deficient mice. The results showed that PYC treatment cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Cold exposure is a wellestablished effective way to stimulate adipose tissue thermogenesis. Several pathways have been identified to contribute to cold exposure-induced UCP-1 expression and subsequent WAT browning (Liu et al, 2019), among which, AMP-activated protein kinase (AMPK) (Lee et al, 2020), sirtuin 1 (SIRT1) (Liao et al, 2018), and protein kinase A (PKA) (Cong et al, 2018) stimulate, while p38 mitogen-activated protein kinase (MAPK) inhibits, white adipose tissue browning (Wang et al, 2019). Obesity adversely impacts these signaling pathways, contributing to defective WAT browning in HFD-induced obesity (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cold exposure is a wellestablished effective way to stimulate adipose tissue thermogenesis. Several pathways have been identified to contribute to cold exposure-induced UCP-1 expression and subsequent WAT browning (Liu et al, 2019), among which, AMP-activated protein kinase (AMPK) (Lee et al, 2020), sirtuin 1 (SIRT1) (Liao et al, 2018), and protein kinase A (PKA) (Cong et al, 2018) stimulate, while p38 mitogen-activated protein kinase (MAPK) inhibits, white adipose tissue browning (Wang et al, 2019). Obesity adversely impacts these signaling pathways, contributing to defective WAT browning in HFD-induced obesity (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…BAT consumes energy by oxidizing fatty acids to generate heat (Qurania et al., 2018). Importantly, browning of WAT promotes energy expenditure through triggering thermogenesis, which suppresses high‐fat diet (HFD)–induced weight gain (Bi et al., 2014; Cong et al., 2018). The current research suggests that browning of WAT might serve as a novel strategy for the prevention of obesity (Baskaran et al., 2016; Guan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the cAMP-dependent pathway, which involves the phosphorylation of PKA, stimulates lipolysis by activating both adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL), which hydrolyze TGs in the lipid droplets of white adipocytes [8,9]. The released free fatty acids can undergo mitochondrial β-oxidation [10], which generates acetyl CoA that is required for WAT browning. Indeed, a recent study showed that PKA activation upregulates UCP1 expression in beige adipocytes [11].…”
Section: Introductionmentioning
confidence: 99%